The Threat of Appendix CITES-Listed Turtles Harvesting in Central Borneo and South Sumatra - Fauzi, Muhammad Alif; Hamidy, Amir; Mumpuni, Mumpuni; Kurniawan, Nia (Journal of Tropical Life Science, 2020)
Exploitation freshwater turtle for local consumption, medicine, and pet in several parts in Asia caused the declining populations in the wild. The purpose of this study is to evaluate of turtle harvest that listed in Appendix CITES in South Sumatra and Central Borneo. We reported the trading network of the three most exploited turtle species in South Sumatera and Central Borneo. We visited the largest middleman in the two provinces and collect the data that comprises the harvest number, prices, trade flow, catching area, and the level of harvest for local consumption. During our survey in Sampit (Central Borneo) (one week in April 2019), we recorded 667 kg of turtles were sent to a middleman and harvested from Jemaras and Sembuluh district. This amount comprises 549 individuals of Cuora amboinensis, 173 Siebenrockiella crassicollis, and one individual of Cyclemys dentata. Contrary to that, in Palembang, we did not find any delivery of turtle from the hunters. However, 387 individuals of C. amboinensis and 132 individuals of S. crassicollis were found in a middleman pool. We also recorded that local people in Central Borneo consumption of turtle meat. The national quota of C. amboinensis in Central Borneo and South Sumatra are 1700 and 2000 individuals for 2019. The national quota of S. crassicollis in South Sumatra is 500 individuals, while Central Borneo does not have any quota for this species. The realization of these wild-caught turtles indicates an over harvesting beyond the annual harvest quota. Moreover, the two middlemen are indicated to carry illegal carapace trading, although the scientific authority recommended to ban the carapace trade.